Design of Lining Structure of Horizontal Swirl Spillway Tunnel. Issue 1 (January 2021) - Zhou, Heng; Xing, Ruijiao; Di, Shengjie; Huang, Peng
Abstract: In this paper, two methods of finite element and structural mechanics are used to study the design of the lining structure of the spillway tunnel, so that the design of each part of the spillway tunnel is economical, reasonable and safe. The finite element method is used to analyze the influence of the surrounding rock consolidation grouting, drainage holes, system bolts and the new and old concrete combination on the bearing capacity of the building. The results show that it is very necessary for the lining structure to be consolidated and grouted, to install system anchor rods and drainage holes. Inserting reinforcement for the old concrete lining is beneficial to improve the stability of the lining structure. Structural mechanics reinforcement can meet the safety and stability requirements of the lining structure.